If it is :
[tex]10 - \frac{ (3x - 1)}{2} = \frac{(6x + 3)}{11} \\ [/tex]
Multiply both sides by 22
[tex](22 \times 10) - 11 \times (3x - 1) = 2 \times (6x + 3) \\ [/tex]
[tex]220 - 33x + 11 = 12x + 6[/tex]
[tex] - 33x + 231 = 12x + 6[/tex]
Plus both sides 33x
[tex]231 = 33x + 12x + 6[/tex]
[tex]231 = 45x + 6[/tex]
Subtract sides minus 6
[tex]231 - 6 = 45x[/tex]
[tex]45x = 225[/tex]
Divided sides by 45
[tex]x = \frac{225}{45} \\ [/tex]
[tex]x = 5[/tex]
_________________________________
If it is :
[tex] \frac{10 - (3x - 1)}{2} = \frac{6x + 3}{11} \\ [/tex]
Multiply sides by 22
[tex](11 \times 10) - 11 \times (3x - 1) = 2 \times (6x + 3) \\ [/tex]
[tex]110 - 33x + 11 = 12x + 6[/tex]
[tex] - 33x + 121 = 12x + 6[/tex]
Plus sides 33x
[tex]121 = 12x + 33x + 6[/tex]
[tex]121 = 45x + 6[/tex]
Subtract sides minus 6
[tex]121 - 6 = 45x[/tex]
[tex]45x = 115[/tex]
[tex]x = \frac{115}{45} \\ [/tex]
[tex]x = \frac{23}{9} \\ [/tex]
_________________________________
And we're done.
Thanks for watching buddy good luck.
♥️♥️♥️♥️♥️